Suicide behavior in pandemia by COVID-19: General overview (Research, Society and Development, 2021)
The purpose of this study was to conduct a literature review with the objective of assessing suicidal behavior during the COVID-19 pandemic. Thus, a search was conducted in the PubMed and Scielo databases for scientific articles published between January 2020 and April 2021. The descriptors used were Suicide and Coronavirus. After applying the inclusion and exclusion criteria, 37 articles were selected. Most of the reviewed studies showed that the pandemic exacerbated some risk factors for suicidal behavior, such as the presence of associated psychiatric disorder, social isolation, unemployment, alcohol use, domestic violence, social stigma, negative news, neurological diseases, sleep disorders, restricted access to health services, and others. Thus, a proportional increase in rates of suicidal behavior is expected during and after the current COVID-19 scenario. Further research is still needed in the area that contributes to the early recognition of risk factors that directly interfere with suicidal behavior. It is important that further studies focus on developing more defined coping strategies to minimize the social, economic, and public health impact of increased suicidal behavior.